Apa yang Memicu Pembelian Impulsif di Shopee? Studi pada Generasi Z di Yogyakarta - Sofyanto, Kurniawan; Transistari, Ralina; Rafinda, Ascariena (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
This study aims to analyze the impact of digital marketing, the use of paylater, and hedonic shopping motivation on online impulse buying in the Shopee marketplace among Generation Z in the Special Region of Yogyakarta. The rapid growth of digital technology, especially in e-commerce, has created new opportunities for businesses to reach consumers, particularly in online shopping platforms like Shopee. The widespread use of digital payment methods, such as paylater, alongside the growing influence of digital marketing and hedonic shopping motivation, has increased impulsive buying behaviors among consumers. Despite the growing attention to online impulse buying, limited research has examined the interplay of these factors specifically within the context of Generation Z in Yogyakarta. This study employs a quantitative approach with survey data collected from Generation Z respondents who have made transactions on Shopee in the past year. The findings suggest that digital marketing, paylater usage, and hedonic shopping motivation all have a significant positive influence on online impulse buying. The study contributes to the existing literature by exploring the combination of these factors in shaping consumer behavior in an increasingly digital marketplace. The results highlight the importance of understanding the unique drivers of impulse buying in the era of e-commerce, providing valuable insights for businesses to improve their marketing strategies and payment solutions.